FROM EAST TOWARD WEST - Naomi ANDO (Journal of Industrial Design and Engineering Graphics, 2019)
In this paper, I would like to overview what I learned from Europe. I havebeen fascinated by European architecture and cities. I have always thought that architecture and cities were interesting because they all have their own places and histories. Here, while adding later analyses and related matters, my first study on European Plazas and the other studies are focused on.